Story of clothes : care for your clothes. Care for the environment - Sen, Benita (New Delhi 9788179935101, 2015)
Prehistoric people made clothes to protect themselves from harsh weather. Since then, clothing has gone through so many changes, the fi rst users of clothes may not recognise them today. From thick animal skins to clever clothes that keep you warm in winter and cool in summer, clothing keeps getting smarter and more fashionable. Although the cloth industry makes a variety of fabrics that are made into clothes, curtains, towels, quilts, and bags that we use everyday, it also uses lots of power to run the looms that make the cloth. The Story of Clothes offers smart, green solutions to practice the 3Rs to green our wardrobes. It also brings you news of green initiatives, like creating synthetic fabric from recycled plastic PET bottles and organic fabrics from soy plants.
Keywords: Clothing